2013
DOI: 10.1007/s00535-013-0819-9
|View full text |Cite
|
Sign up to set email alerts
|

Precise evaluation of liver histology by computerized morphometry shows that steatosis influences liver stiffness measured by transient elastography in chronic hepatitis C

Abstract: A precise evaluation of liver histology by computerized morphometry shows that liver stiffness measured by Fibroscan is linked to liver fibrosis, activity, and also steatosis. High level of steatosis induces misevaluation of liver fibrosis by Fibroscan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 40 publications
1
43
2
Order By: Relevance
“…They found that 12.6% of F0/1 were misclassified as F2 when the steatosis area of the liver specimen (area of steatosis vesicles over complete liver surface estimated by morphometry) was < 4.0 %. When the steatosis area was ≥ 4%, the rate of misclassification rose to 32.4% 60. However, other studies suggested that presence of steatosis did not influence fibrosis estimation.…”
Section: Clinical Applications Of Ultrasound Elastographymentioning
confidence: 90%
“…They found that 12.6% of F0/1 were misclassified as F2 when the steatosis area of the liver specimen (area of steatosis vesicles over complete liver surface estimated by morphometry) was < 4.0 %. When the steatosis area was ≥ 4%, the rate of misclassification rose to 32.4% 60. However, other studies suggested that presence of steatosis did not influence fibrosis estimation.…”
Section: Clinical Applications Of Ultrasound Elastographymentioning
confidence: 90%
“…However, several factors may influence TE values in assessing the degree of fibrosis such as the presence of steatosis, 39 a standardized meal before TE, 40 , 41 and alcohol consumption 42 …”
Section: Discussionmentioning
confidence: 99%
“…4 Some studies also used image analysis of liver tissue to evaluate correlations between the proportion of whole collagen fibrosis and transient elastography. 27,[38][39][40] Wong et al 27 observed in an univariate analysis that 'pericellular fibrosis' better correlated with liver stiffness measurement than 'periportal' or 'perivenular fibrosis,' especially in patients with severe fibrosis. This study and ours are barely comparable, because of size difference and different methodology.…”
Section: Discussionmentioning
confidence: 99%